A Study on the Relationship Among Brand Image, Service Quality, Customer Satisfaction, and Customer Loyalty – Taking ‘the Bao Wei Zhen Catering Team’ As an Empirical Study - Hsieh, S-W; Lu, C-C; Lu, Y-H (KnE Social Sciences, 2018)
This research focused on the industries of catering services and took the Bao Wei Zhen Catering Team, for example, to explore the relationship between ‘brand image’, ‘service quality’, ‘customer satisfaction’, and ‘customer loyalty’. It was meant to found out the important factors affecting consumer satisfaction and the words of mouth. From this research, it could be found that service quality exerted very important influence on the culture of traditional catering services. That was to say when service quality was good, not only the brand image could be improved but also customer satisfaction would be enhanced. Therefore, if it was necessary to further improve the competitiveness of traditional catering service industries, the improvement of service quality was required. Through the improvement of service quality, the current plight faced by the culture of catering services could be effectively improved. Keywords: brand image, service quality, customer satisfaction, customer loyalty, catering team